SOCIODEMOGRAPHIC PECULIARITIES AND LIVELIHOOD PRACTICES OF FARMERS IN SELECTED RIVERINE ISLANDS: A MIXED METHODS INSIGHT FROM BANGLADESH - Barau Aliyu Akilu; Afrad Md Safiul Islam; Halim Abdul; Rahman G.K.M. Mustafizur (Natural Resources and Sustainable Development, 2023)
Living on Bangladesh’s riverine islands (Char lands) puts one at the disadvantage of underdevelopment. Hence, this study focused on the sociodemographic peculiarities and livelihood practices of farmers in the Char lands of Bangladesh. Convergent mixed methods research design was adopted to generate the required data. The quantitative data were analyzed using Statistix 10 software, while the qualitative data were analyzed by collecting themes relative to the study objectives and describing them accordingly. Results revealed that, the sociodemographic peculiarities of the respondents were low and vulnerable, being majority illiterate, having small farm size on which they predominately depend, poor housing, and a population dominated by ≥ 30 years old persons. The mean income (%) from on-farm livelihood practices was superior to that from off-farm livelihood practices, and a big proportion of the mean annual expenditure coverage was split between food and agricultural inputs/implements. Farm size contributes significantly to income, but, natural disaster, illiteracy, riverbank erosion, and lack of improved agriculture knowledge were the foremost livelihood problems in the Char lands. Consequently, the present study deduces that an all-inclusive masterplan is inevitable for sustainable development of the Bangladesh Char lands.